Comparative phytochemical composition, oleuropein quantification, antioxidant and cytotoxic properties of Olea europaea L. leaves. Issue 6 (19th March 2023) - Anwar, Sirajudheen; Saleem, Hammad; Khurshid, Umair; Ansari, Shabana Yasmeen; Alghamdi, Saleh; Al-Khulaidi, Abdul Wali A.; Malik, Jonaid Ahmad; Ahemad, Nafees; Awadh Ali, Nasser A.
Abstract: In the present research, oleuropein (OLE) contents from two Saudi Arabian wild olive trees ( Olea europaea L.) leaves (O1 and O2), were collected from two nearby geographical sites differing in altitudes, and were determined via UHPLC-MS analysis. Moreover, total bioactive contents, antioxidant, and cytotoxicity (against MCF-7 and MDA-MB-231 cells) potential were also evaluated. The sample (O2) was found to contain significantly ( p < 0.05) higher OLE content (4.13 ± 1.0 mg/g DW) compared with the sample (O1) having OLE content (3.63 ± 1.1 mg/g DW). A similar trend was observed regarding total bioactive contents and antioxidant potential. However, both samples exhibited low cytotoxicity against tested cell lines. Furthermore, with hierarchical cluster analysis that compared the results of our samples (O1 and O2) to other samples reported in the literature, it was found that the variance in OLE content and biological activities from Al Baha region leaves had a resemblance to other reported superior cultivars. Graphical Abstract: UF0001